Effects of 360° TitaniUM Core Strength Exercise on physical performances and low back pain in amateur table tennis players - Ling, Ling Lai; Chen, Soon Chee; Samsudin, Shamsulariffin; Zamri, Fatin Nur Shahira; Boon, Hooi Lim (Codon Publications, 2023)
This studyinvestigatedthe effectsof the 360° TitaniUM Core Strength Exercise© on thephysical performances of amateur table tennis (TT) players withinthe Malaysian public sector and its potential to reduce the risk of low back pain (LBP).Twenty participants were recruited from various government departments in Negeri Sembilan. They were randomly assigned to either the core exercise group (CE) or the control group (CON). The CEgroup underwent a six-week intervention featuring the 360° TitaniUM Core Strength Exercise©, while the CONgroup followed their usual routine. Physical performanceswere assessed using isometric endurance, flexibility, strength, balance, and stability tests, whereas LBP was measured throughthe Visual Analog Scale (VAS). The results exhibitedsignificant improvements in CE group's isometric endurance, flexibility, and strength (p< .05), along with notable enhancements in trunk balance and stability.Furthermore, the CE group demonstrated a trend towards reduced LBP risk as indicated by VAS scores (p< .05). These findings suggest that the 360° TitaniUM Core Strength Exercise© holds promise for enhancing physical performancesand potentially mitigating LBP among amateur TT players in the Malaysian public sector. Further research could explore long-term effects anditspotential applications across diverse populations and sports disciplines.